2006
DOI: 10.1097/00131746-200607000-00004
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot, Open-Label Safety Study of Quetiapine for Treatment of Moderate Psychotic Agitation in the Emergency Setting

Abstract: Quetiapine demonstrated some efficacy as a sedative agent in the emergency setting, although no clear dose-response pattern emerged over the narrow dose range tested. Orthostasis was common and did not correlate with dosing. This small study did not support the use of quetiapine to treat acute agitation in potentially volume-depleted patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Since aripiprazole and olanzapine have been shown to be effective in monotherapy this should not be a frequent problem. In a small open-label study of quetiapine, orthostasis was present in 40% of patients at 100-200 mg doses (Currier 2006a).…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Since aripiprazole and olanzapine have been shown to be effective in monotherapy this should not be a frequent problem. In a small open-label study of quetiapine, orthostasis was present in 40% of patients at 100-200 mg doses (Currier 2006a).…”
Section: Safetymentioning
confidence: 99%
“…However, 93% of patients prefer oral formulations during a behavioural emergency, perceiving parenteral administration as coercive and abusive (Altamura 2003). Recent literature has shown that, for patients willing to take them, oral atypical antipsychotics are at least as effective as intramuscular typical antipsychotics in acute psychotic agitation (Currier 2006a). They should therefore be the first-line method of pharmacological administration (Mohr 2005).…”
Section: Pharmacological Interventions (Rapid Tranquillisation)mentioning
confidence: 99%
“…36 Second, research on quetiapine has indicated that while this medication is useful in inpatient settings, it has an unacceptably high risk of orthostatic hypotension in the emergency department where patients are often volume depleted. 41 Third, clozapine is only FDA approved for treatment-resistant schizophrenia and is not generally a first-line agent. Thus, although more study is needed, the use of aripiprazole, quetiapine, or clozapine cannot be recommended as first-line agents in the acute control of agitation.…”
Section: The Use Of Second-generation Antipsychoticsmentioning
confidence: 99%
“…Quetiapine, in particular, imposes an unacceptably high risk of orthostatic hypotension and so is not recommended for use in delirium in the emergency department. 27 Additionally, quetiapine is anticholinergic, raising concerns about constipation and urinary retention.…”
Section: Atypical Antipsychoticsmentioning
confidence: 99%